2019
DOI: 10.3892/ijmm.2019.4393
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol antagonizes doxorubicin‑induced cardiomyocyte senescence by inhibiting TXNIP‑mediated NLRP3 inflammasome activation

Abstract: Senescence of cardiomyocytes is considered a key factor for the occurrence of doxorubicin (Dox)-associated cardiomyopathy. The NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome is reported to be involved in the process of cellular senescence. Furthermore, thioredoxin-interactive protein (TXNIP) is required for NLRP3 inflammasome activation and is considered to be a key component in the regulation of the pathogenesis of senescence. Studies have demonstrated that pretreatment with honokiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Moreover, supporting action on islet biology was concurrently revealed in another study through reversion of impaired endothelial cell angiogenic function, generation of VEGF, and sensitivity to VEGF activities [ 26 , 64 ]. Recently, TXNIP-knockdown has shown improved anti-senescence and anti-inflammation effects on H9c2 cardiomyocytes under doxorubicin-associated cardiomyopathy [ 70 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…Moreover, supporting action on islet biology was concurrently revealed in another study through reversion of impaired endothelial cell angiogenic function, generation of VEGF, and sensitivity to VEGF activities [ 26 , 64 ]. Recently, TXNIP-knockdown has shown improved anti-senescence and anti-inflammation effects on H9c2 cardiomyocytes under doxorubicin-associated cardiomyopathy [ 70 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…18 We further demonstrated that HNK inhibits T cell proliferation and dendritic cell differentiation. 19 Consistently, HNK has also been shown to preserve mitochondria and to protect the heart in cardiomyopathy 20,21 and the liver in bacterial infection 22 in mice.…”
Section: Introductionmentioning
confidence: 88%
“…Conversely, TXNIP has a pro-inflammatory role leading to cardiac, vascular and endothelial dysfunctions [ 13 , 19 , 21 , 66 , 67 , 68 , 143 , 144 ]. Numerous studies conducted since the 2000s suggest that TXNIP may bind to the NLRP3 inflammasome, which enhances the inflammatory response, as reviewed almost a decade ago [ 65 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] and summarized in Figure 1 . TXNIP and NLRP3 physically interact to activate the inflammasome [ 83 ].…”
Section: Txnip Is a Multifunctional Proteinmentioning
confidence: 99%
“…The expression of inflammatory markers and adhesion molecules such as ICAM-1, VCAM-1, and MCP-1 are diminished in VSMCs from TXNIP knockout mice [ 110 ]. This inflammation state can trigger cell senescence or cell death characterized as pyroptosis, which is hampered with the decrease of TXNIP [ 66 , 78 , 92 , 93 , 105 ]. The ROS-TXNIP-NLRP3 pathway can actually be enabled for a long time via an IL-1β-mediated positive feedback loop [ 145 ].…”
Section: Txnip Is a Multifunctional Proteinmentioning
confidence: 99%